2013
DOI: 10.1108/13563281311294146
|View full text |Cite
|
Sign up to set email alerts
|

Organizational communication in Malaysia organizations

Abstract: Purpose -Research on organizational communication has shown significant associations with many important outcomes. Although these researches are appealing, there have been criticisms and suggestions for improvement of the organizational communication scales, developed in Western organization settings, to make them applicable to collectivist culture-based organizations. Therefore, the purpose of this paper is to access the organizational communication construct through the development and validation of an organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Among the studies than used factor analysis, the majority chose to use EFA (e.g., Bakar and Mustaffa 2013;Turker 2009). Similar to our findings, Bastos et al (2010) and Ladhari (2010) found EFA to be the more commonly utilized construct validity method when compared to CFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies than used factor analysis, the majority chose to use EFA (e.g., Bakar and Mustaffa 2013;Turker 2009). Similar to our findings, Bastos et al (2010) and Ladhari (2010) found EFA to be the more commonly utilized construct validity method when compared to CFA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the inadequate choice of the instruments or variables to be correlated with the variable of interest was another psychometric limitation cited in some studies (e.g., Bakar and Mustaffa 2013;Tanimura et al 2011). This kind of limitation directly affects the convergent validity, which is a problem since, as has already been shown in this review, this type of validity has been one of the most recurrent practices in scale development.…”
Section: Ten Main Limitations Reported In the Scale Development Procementioning
confidence: 99%
“…Many researchers have argued that the combination of both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) is an efficient way to evaluate the measurement scale or theory. In most of the studies in scale development, the majority of the researchers have chosen EFA as the best way to check the construct validity rather than CFA (Bakar and Mustaffa, 2013). The data analysis has been carried through the application of the IBM-SPSS 21 version.…”
Section: Approach Of Scale Developmentmentioning
confidence: 99%
“…These values diverge with that of westerners, which emphasise on assertiveness, independence, aggressiveness and competitiveness. Hassan and Che Su (2013) Malaysian organisations, collective bond and mutual respect are salient work relationships.…”
Section: The Malay Ethnic Communication Characteristicsmentioning
confidence: 99%